The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2478/s13382-013-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender differentiation of indirect self-destructiveness

Abstract: Objectives: The objective of this study was to examine the sex (gender) differentiation of indirect self-destructiveness intensity and its manifestations, as well as relationships between indirect self-destructiveness and its manifestations (categories) and the psychological dimensions of masculinity and femininity, also from the point of view of assessing occupational health and safety. Materials and Methods: A population of 558 individuals (399 females and 159 males) aged 19-25 (mean age: 22.6) was studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(47 citation statements)
references
References 13 publications
2
37
1
7
Order By: Relevance
“…Females scored higher on poor health maintenance (A2) and males scored significantly higher on three categories: personal and social neglects (A3), lack of planfulness (A4), and helplessness (A5). Results were similar in the general population (of individuals who did not attempt suicide) with the difference being that in the general population males scored significantly higher also on poor health maintenance (A2) [14]. As it can be seen, the result is opposite in the group of females who attempted suicide.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Females scored higher on poor health maintenance (A2) and males scored significantly higher on three categories: personal and social neglects (A3), lack of planfulness (A4), and helplessness (A5). Results were similar in the general population (of individuals who did not attempt suicide) with the difference being that in the general population males scored significantly higher also on poor health maintenance (A2) [14]. As it can be seen, the result is opposite in the group of females who attempted suicide.…”
Section: Discussionmentioning
confidence: 60%
“…It is worth pondering over the fact that although in the general population (with no suicide attempts) the intensity of indirect self-destructiveness, as a generalised behavioural tendency, is higher in males [14], the received results reveal that it is equal in males and females who attempted suicide. Could females who attempted suicide “catch up” with males in respect of indirect self-destructiveness?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among men, masculinity is directly associated with fewer receipt of healthcare and particularly mental health services (15)(16)(17)(18). Young adult men (aged 19-15 years) are significantly less likely to self-provide health maintenance than females, and this is directly associated to strength of their masculine self-conceptions (19). Public health interventions targeting misconceptions among males that a lifestyle involving poor self-care is masculine may be of value.…”
Section: Societal Factorsmentioning
confidence: 98%
“…1, 12]. Most of the carried out research concerned direct self-destructiveness; it was found, for instance, that women exhibit passive self-destructiveness [13].…”
Section: Introductionmentioning
confidence: 99%